Wettbewerbsbeziehungen im Güterverkehr. - Eisenkopf, Alexander; Hahn, Carsten; Schnöbel, Christian R. (Deutscher Verkehrs-Verl., 2008)
Der Wettbewerb zwischen Straßen- und Schienengüterverkehr und seine möglichen Verzerrungen stehen seit Jahren im Fokus der verkehrspolitischen Diskussion. Gängige These ist, dass der Schienenverkehr infolge intermodaler Wettbewerbsverzerrungen gegenüber dem Straßenverkehr benachteiligt sei. Solche Benachteiligungen setzen aber voraus, dass Schienengüterverkehr (SGV) und Straßengüterverkehr (StGV) auf einem gemeinsamen Markt agieren. Erstaunlicherweise wurden aber erst in jüngerer Zeit Studien zur Abgrenzung entsprechender relevanter Märkte vorgelegt und das auch nur vereinzelt.

This investigation deals with the competition between freight transport by road (StGV) and rail (SGV). The identification of a chosen market from the aspect of freight carrier substitution in line with demand has shown that both the StGV and SGV cannot function together within a common market set-up due to their vastly divergent system-specific characteristics and the requirements of forwarders. This makes it necessary to differentiate between market segments. The transport of consolidated consignments by road cannot be substituted by the SGV while, in turn, bulk cargo transport by rail cannot be substituted by the StGV. Competition is only evident in the field of freight traffic. Due to the limited substitution potential, distorted competition loses its significance. Evidence of this is minimal although emphasized elsewhere to the contrary. Transport cost charges and the allocation of public investment funds tend to work out in favour of the SGV rather than to its disadvantage. The internal distribution ofexternal costs creates distortion that affects the SGV unfavourably. This must not be over-estimated since it affects only a small part of the common market where rates are a less determinant factor. Accordingly, intra-modal competition gains significance since it is less evident in the case of the SGV than in the case of the StGV. The SGV has progressed positively because of the expanded scope of its operations, helped by the contribution made - amongst others - by private rail carriers that are faced with distorted competition in the same way as the DB AG. They have, nonetheless, successfully gained market access, which is proof of inter-modal distorted competition being of little significance.
Competition in freight transport markets.
Keywords: Verkehr; Güterverkehr; Schienengüterverkehr; Straßengüterverkehr; Verkehrsnachfrage; Wettbewerb; Verkehrswirtschaft; Verkehrsplanung; Verkehrsmarkt; Verkehrsleistung; Verkehrsforschung; Verkehrsangebot